2010
DOI: 10.1111/j.1476-5381.2010.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of the R2 peptide, an inhibitor of transglutaminase 2, in a mouse model of allergic asthma, induced by ovalbumin

Abstract: BACKGROUND AND PURPOSETransglutaminase 2 (TGase 2) expression is increased in inflammatory diseases, and TGase 2 inhibitors block these increases. We examined whether the R2 peptide inhibited the expression of TGase 2 in a mouse model of inflammatory allergic asthma. EXPERIMENTAL APPROACHC57BL/6 mice were sensitized and challenged by ovalbumin (OVA) to induce asthma. OVA-specific serum IgE and leukotrienes (LTs) levels were measured by enzyme-linked immunosorbent assay. Recruitment of inflammatory cells into b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 57 publications
(78 reference statements)
1
45
0
Order By: Relevance
“…In the mouse, daily intraperitoneal administration of a TG2 peptide inhibitor (KVLDGQDP) is reported to block OVA-induced lung inflammation (64,65). In these studies, the cellular targets of the TG peptide inhibitor are not known.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the mouse, daily intraperitoneal administration of a TG2 peptide inhibitor (KVLDGQDP) is reported to block OVA-induced lung inflammation (64,65). In these studies, the cellular targets of the TG peptide inhibitor are not known.…”
Section: Discussionmentioning
confidence: 98%
“…A TG2 peptide inhibitor (KVLDGQDP) administered by daily intraperitoneal injection is reported to block OVA-induced lung expression of TG2, VCAM-1, IL-4, IL-5, and IL-13 (64,65). In contrast to these studies with a peptide and unknown cellular targets of the peptide, we report that supplementation with 5-HTP did not alter OVA-induced lung tissue mRNA expression of adhesion molecules, cytokines, chemokines, or chemokine receptors, including lung tissue expression for the Th2 cell cytokines IL-4 and IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…Further activation of the mature sPLA 2 -X protein may also be important in asthma, as we previously found that transglutaminase 2 is overexpressed in the airways of patients with asthma and increases the enzymatic activity of human sPLA 2 -X (38). A dual inhibitor of transglutaminase 2 and sPLA 2 in the lipocortin family inhibited the development of inflammation and AHR in a murine model of asthma (39). Although the expression of PLA2G10 was much higher in epithelial cells than other airway cells, it is possible that the elevated level of sPLA 2 -X is due to secretion of the protein from a nonepithelial source.…”
Section: Discussionmentioning
confidence: 99%
“…TGaseII expressed in mast cells enhances IgE level in B cells by regulating CD40L (14). R2 peptide, an inhibitor of TGaseII, reduces * This work was supported by National Research Foundation Grants allergic responses by regulating NF-B/TGaseII activity in a mouse model of allergic asthma (15). Octapeptide R2 (KVLDGQDP), which has anti-transglutaminase (TGase) activity, decreases inflammation in an allergic conjunctivitis model in guinea pigs (16).…”
mentioning
confidence: 99%